2020
DOI: 10.1155/2020/3896263
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Urinary Proteomic Signature for Differential Diagnosis of Acute Appendicitis

Abstract: Acute appendicitis is one of the most common acute abdomens, but the confident preoperative diagnosis is still a challenge. In order to profile noninvasive urinary biomarkers that could discriminate acute appendicitis from other acute abdomens, we carried out mass spectrometric experiments on urine samples from patients with different acute abdomens and evaluated diagnostic potential of urinary proteins with various machine-learning models. Firstly, outlier protein pools of acute appendicitis and controls were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…LR followed in frequency, appearing in nine studies [ 3 , 24 26 , 28 , 30 , 32 , 42 , 43 ]. DT [ 25 , 30 , 35 , 36 , 40 , 41 , 43 ] and SVM [ 23 , 24 , 28 , 30 , 37 , 45 ] were each utilized in seven studies, while RF [ 23 , 24 , 29 , 31 , 45 ] was implemented in six studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LR followed in frequency, appearing in nine studies [ 3 , 24 26 , 28 , 30 , 32 , 42 , 43 ]. DT [ 25 , 30 , 35 , 36 , 40 , 41 , 43 ] and SVM [ 23 , 24 , 28 , 30 , 37 , 45 ] were each utilized in seven studies, while RF [ 23 , 24 , 29 , 31 , 45 ] was implemented in six studies.…”
Section: Resultsmentioning
confidence: 99%
“…Radiological assessments, particularly CT images, were the chosen input modality in three studies [ 12 , 20 , 22 ]. Laboratory data served as the exclusive input for four studies [ 19 , 23 , 32 , 36 ]. Additionally, three studies deployed a combination of clinical observations and laboratory data as their input features [ 38 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…We concluded that no suitable threshold was found in the dataset subjected to PCA and therefore applied six machine learning algorithms, which are used for and are familiar to researchers in the proteomics field 13 20 , to classify the peptide peaks from the dataset. A total of 737 peaks, including 380 peptide and 357 noise peaks, were divided into a training set (418 data peaks; 219 peptide and 199 noise peaks) and a test set (319 data peaks; 161 peptide and 158 noise peaks) and then independently analyzed with the six different supervised machine learning algorithms using the dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Some recent investigations have used machine learning techniques to identify peptide peaks from large datasets and classify proteins in comparative analyses 13 20 . A mass precision algorithm was developed to extract the signal from the noise, thus improving quantitation using a random forest (RF) classifier and heuristic score 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This upregulation of APOC1 could potentially indicate the presence of a bacterial infection in Acute Appendicitis, distinguishing it from other conditions within the CON group, such as cholecystitis and pancreatitis. 128,129 A study conducted using LC-MS/MS by Berbee et al found that APOC1 (apolipoprotein C1) is upregulated in acute appendicitis. 129 Allister et al studied serum concentrations of C-reactive protein (CRP) and granulocyte colonystimulating factor (GCSF) and detected a substantial difference between patients with acute appendicitis and healthy controls.…”
Section: Diagnostic and Prognostic Biomarker For Other Diseasesmentioning
confidence: 99%